2021
DOI: 10.1007/s10826-021-01915-5
|View full text |Cite
|
Sign up to set email alerts
|

How do Saudi Children and Their Mothers Evaluate Religion-Based Exclusion?

Abstract: This study focuses on Saudi mothers’ and their children’s judgments and reasoning about exclusion based on religion. Sixty Saudi children and their mothers residing in Saudi Arabia and 58 Saudi children and their mothers residing in the United Kingdom were interviewed. They were read vignettes depicting episodes of exclusion based on the targets’ religion ordered by peers or a father. Participants were asked to judge the acceptability of exclusion and justify their judgments. Both groups rated the religious-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…Finally, although fewer studies have focused on social class, one study found that most Nepalese adolescents (ages 12-15 years) thought that a rich parent would not want their child to be friends with a poor peer (Grütter et al, 2021). These perceptions have an impact; children and adolescents who perceive their own parents to be hesitant about outgroup peers find it more acceptable to socially exclude someone who is different from them in race (ages 14-17 years; Edmonds & Killen, 2009), nationality (ages 14-17 years; Brenick & Romano, 2016), or religion (ages 8-12 years; Alsimah et al, 2021). Given the importance of positive intergroup interactions for social and emotional well-being in childhood and adolescence (Tropp et al, 2022), this points to a serious lack of perceived parental support for such interactions among youth.…”
Section: Youth Perceptions Of Parental Comfort With Intergroup Peer I...mentioning
confidence: 99%
“…Finally, although fewer studies have focused on social class, one study found that most Nepalese adolescents (ages 12-15 years) thought that a rich parent would not want their child to be friends with a poor peer (Grütter et al, 2021). These perceptions have an impact; children and adolescents who perceive their own parents to be hesitant about outgroup peers find it more acceptable to socially exclude someone who is different from them in race (ages 14-17 years; Edmonds & Killen, 2009), nationality (ages 14-17 years; Brenick & Romano, 2016), or religion (ages 8-12 years; Alsimah et al, 2021). Given the importance of positive intergroup interactions for social and emotional well-being in childhood and adolescence (Tropp et al, 2022), this points to a serious lack of perceived parental support for such interactions among youth.…”
Section: Youth Perceptions Of Parental Comfort With Intergroup Peer I...mentioning
confidence: 99%
“…In addition, children and adults recruit other types of reasons to situations that may also be deemed involving physical and/or psychological harm (Alsimah et al, 2021). For example, young people often invoke dimensions related to psychological aspects (referring to psychological aspects of the actors involved), outcomes (concerning the consequences of the situation), physical (referring to physical aspects of the situation), and authority (concerning aspects related to hierarchy and power) in situations in which exclusion and rights are entailed (Alsimah et al, 2021). Because social knowledge is embedded in social situations, people often negotiate their understanding of a situation with recourse to multiple domains of reasoning (Besiveric & Turiel, 2020; Ruck & Tenenbaum, 2014).…”
Section: Social Domain Theorymentioning
confidence: 99%
“…The present study focuses on parent–child emotion talk because everyday conversations support children in appropriating the cultural norms of their communities (Aznar & Tenenbaum, 2015; Tenenbaum & Hohenstein, 2016). Through conversations parents socialize children’s general emotion understanding (Aznar & Tenenbaum, 2013, 2020; Laible & Song, 2006), moral understanding (Eisenberg, 2000), and values (Alsimah et al, 2021). After controlling for children’s previous emotion understanding, mothers’ use of emotion words in conversations with their children predicted children’s future emotion understanding (Aznar & Tenenbaum, 2013).…”
Section: Social Domain Theorymentioning
confidence: 99%